A QUALITATIVE ANALYSIS ON THE APPLICATION OF TEMPO ON THE CHOIR SONGS WITHOUT TEMPO MARKINGS - Mamantung, Rena Maria; Sri Hartati, R. A. Dinar; Takalumang, Luccylle M. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This research was conducted with the aim of understanding and explaining how tempo is applied in singing choir songs that do not have tempo markings. Tempo, in this context, refers to the speed or slowness with which a musical composition is sung, either by human vocals or musical instruments. To measure the speed of a song, a tool called a Maezel Metronome is used. Tempo markings can be classified into several groups, such as very slow, not very slow, medium, fast, and very fast tempos. This study is conducted using the qualitative research method in which the data collection is carried out through library research and observation. The obtained data are then validated through the process of categorization, editing, analysis and conclusion. The validated data are analyze using he theory of tempo proposed by Perry Rumengan. This research uses a qualitative descriptive method with data collection techniques through literature study and observation. The research results show that tempo has an important role in the context of choirs. In applying tempo to Choir songs, it is necessary to pay attention to the meaning of the lyrics, the ideas conveyed, the melody and rhythm movement, the time structure, expression techniques, as well as the style and genre of the music concerned.